Modelling Structural and Macroeconomic Drivers of Disparities in the Energy–Growth Nexus in Sub-Saharan Africa - Azubuike, Nyeso Christian; Ikiensikimama, Sunday Sunday; Osokogwu, Uche (International Journal of Energy Economics and Policy, 2026)
The energy–growth–environment nexus has long been central to debates on sustainable development, yet empirical evidence for Sub-Saharan Africa (SSA) remains fragmented and inconclusive. While earlier studies have explored the impact of energy consumption on growth, limited attention has been given to the drivers of disparities in the nexus across SSA. This gap is particularly significant given the region heterogeneous economic structures, resource endowments, and demographic dynamics. This study investigates the structural and macroeconomic determinants of disparities in the energy–growth relationship across 41 SSA countries between 1990 and 2024. Specifically, it examines how factors such as human development, labour force participation, unemployment, population growth, and foreign direct investment (FDI) interact with energy use to influence economic growth. A dynamic linear growth model is estimated using the Sequential Two-Stage Generalized Method of Moments (GMM). The results show weak evidence of growth persistence, as lagged GDP coefficients were positive but statistically insignificant. Total energy consumption also proved insignificant, suggesting that energy expansion alone does not directly drive growth in SSA. By contrast, the human development index exhibited a strong and significant positive effect, underscoring the centrality of human capital to long-run growth. Labor force participation contributed positively with marginal significance, while unemployment had a slight but negative impact, reflecting structural labour market inefficiencies. Population growth and FDI were both insignificant, pointing to demographic pressures and limited absorptive capacity. These findings highlight the need for integrated policy frameworks that prioritize human capital investment, labour market reforms, expansion in renewable energy access, institutional strengthening, and demographic management. A key limitation of the study is the exclusion of some country-specific structural factors, such as governance, geography and natural endowments. Future research should incorporate these variables and explore country-level asymmetries to better inform targeted policy formulation.